Effect of zinc ion substitution on sodium-nickel-manganese materials as cathode materials - Izaak, Maya Puspitasari; Gunanto, Yohanes Edi; Sitompul, Henni; Purwamargapratala, Yustinus (Jurnal Fisika dan Aplikasinya, 2023)
Sodium is one of the new materials to replace Lithium in battery manufacture. For this reason, further research is needed to explore this new material and its composition that meets the cathode material standards. This research aims to synthesize and characterize the Sodium-Nickel-Manganese material with the Zn2+ combination, which is expected to be used as a battery cathode material. The characterization used is XRD, SEM, and LCR-meter. In this research, we succeeded in synthesizing and characterizing Sodium-Nickel-Manganese material with a particle size of around 250-500 nm. Characterization using an LCR meter obtained conductivity values of 6.77 ×10-6,7.46×10-4 and 5.45×10-2S/cm at 100 Hz, 1.86 ×10-6,8.75×10-4 and 1.16 S/cm at 1.5 KHz, 1.7 ×10-6,9.45×10-4 and 1.51 S/cm at 3 KHz, for Zn2+ substitution with x=0.1, 0.15, and 0.20, respectively.